Evaluasi Tarif AKDP rute Surabaya-Malang Kelas Ekonomi Berdasarkan Abillity To Pay dan Willingness To Pay - Rizkiyani Rosida, Ismi; Maria Chandra Agusdini, Theresia (Jurnal Etnik: Ekonomi-Teknik, 2023)
Public transportation is one of the transportation used by the public in making movements. In urban areas with high generation and pull must be balanced with the availability of public transportation. Public transportation is said to be successful if many people use it. Fares are one of the considerations of the community in choosing public transportation. Due to the increase in fuel prices, it has an impact on the increase in public transportation fares for the Surabaya-Malang route. Therefore, it is necessary to evaluate the tariff increase to determine the ability and willingness of the people who use public transportation on the Surabaya-Malang route so that no related parties are harmed. The calculation of rates based on Abillity To Pay (ATP) and Willingness To Pay (WTP) is based on quantitative analysis.Based on the calculation of Abillity To Pay (ATP) on weekdays a tariff of IDR 28,563.92 is obtained and on holidays a tariff of IDR 20,311.27 is obtained while based on Willingness To Pay (WTP) on weekdays a tariff of IDR 19,088.07 is obtained and on holidays a tariff of IDR 18,253.69 is obtained. While the tariff applied at the time of research was IDR 20,000. ATP values on weekdays and holidays are higher than the rates applied at the time of the study so that the rates applied do not exceed the user's ability. Meanwhile, the WTP value on weekdays and holidays is lower than the tariff applied at the time of the study, so service providers must improve public transportation services.